2017
DOI: 10.1089/jir.2017.0069
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Prevents Osteoarthritis by Inhibiting the Activation of Inflammasome NLRP3

Abstract: Curcumin has shown protective potential on osteoarthritis. However, its effect on treatment of osteoarthritis remains elusive so far. This study aimed to determine whether curcumin could ameliorate osteoarthritis in vivo and the underline mechanisms. The mice subjected to destabilization of the medial meniscus (DMM) surgery were administered curcumin. Cartilage integrity was evaluated by immunohistological staining. Expression levels of inflammatory cytokines from mice arthrodial cartilage were detected. THP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 31 publications
2
47
0
2
Order By: Relevance
“…NLRP3 may serve as a potential biomarker for the management of OA [26]. Inhibition of NLRP3 inflammasome by curcumin or estradiol could downregulate inflammatory cytokines and prevent OA progress [27,28]. In the present study, ICA attenuated LPSinduced inflammation and pyroptosis by inhibiting NLRP3 inflammasome signaling, and the overexpression of NLRP3 reduced the protective effect of ICA.…”
Section: Discussionsupporting
confidence: 49%
“…NLRP3 may serve as a potential biomarker for the management of OA [26]. Inhibition of NLRP3 inflammasome by curcumin or estradiol could downregulate inflammatory cytokines and prevent OA progress [27,28]. In the present study, ICA attenuated LPSinduced inflammation and pyroptosis by inhibiting NLRP3 inflammasome signaling, and the overexpression of NLRP3 reduced the protective effect of ICA.…”
Section: Discussionsupporting
confidence: 49%
“…These results indicated that 4′MR might be involved in RAGE receptor-ligand axis via inhibiting RAGE expression. Certain natural substances such as curcumin have been proven to own anti-inflammatory activity by suppressing AGE-RAGE associated vascular injury and long-term complications of diabetes [ 24 ]. Therefore, the inhibition of inflammatory processes induced by AGEs-RAGE axis was considered as a good potential intervention target for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abnormal activation of the inflammasome will lead to harmful overwhelming inflammation, which may damage the infected tissue. Persistent and abnormal NLRP3 signaling is the basis of many chronic and degenerative diseases, including Stargardt disease type 1 [82], Alzheimer's disease [83], atherosclerosis [84], atrial fibrillation [85], osteoarthritis [86], and cancer [87] ( Table 1).…”
Section: The Crosstalk Between Nlrp3 and Autophagymentioning
confidence: 99%